2021
DOI: 10.3389/fpsyt.2021.728971
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Correlation of Decayed, Missing, and Filled Teeth in Elderly Inpatients With Schizophrenia

Abstract: Introduction: Schizophrenia is a mental disease with a profound impact on human health. Patients with schizophrenia have poor oral hygiene, increasing their risk of systemic diseases, such as respiratory infections, and declining their quality of life. Therefore, this study aims to assess the oral health status of inpatients with schizophrenia, analyze its related factors, and thus provide scientific evidence for further exploration of corresponding control strategies.Methods: A total of 425 inpatients older t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…The prevalence of underweight was higher among our Japanese inpatients with schizophrenia (17.0%) compared with the prevalence reported in previous studies of Taiwanese (4.3%) 11 and Chinese (6.6%) samples. 12 Previous large-scale studies reported that the prevalence rates of underweight were 20.2% and 17.4% in 15,171 and 14,237 Japanese inpatients with schizophrenia, respectively. 15 , 16 Additionally, a meta-analysis indicated an odds ratio of 4.4 for underweight in Japanese inpatients with schizophrenia.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The prevalence of underweight was higher among our Japanese inpatients with schizophrenia (17.0%) compared with the prevalence reported in previous studies of Taiwanese (4.3%) 11 and Chinese (6.6%) samples. 12 Previous large-scale studies reported that the prevalence rates of underweight were 20.2% and 17.4% in 15,171 and 14,237 Japanese inpatients with schizophrenia, respectively. 15 , 16 Additionally, a meta-analysis indicated an odds ratio of 4.4 for underweight in Japanese inpatients with schizophrenia.…”
Section: Discussionmentioning
confidence: 97%
“…This score significantly differed in 878 Taiwanese inpatients with schizophrenia, 11 but not in 425 Chinese inpatients with schizophrenia. 12 Although the Decayed-Missing-Filled Teeth score is a standard index for assessing dental status, it is difficult for psychiatrists and nurses to measure this score in real-world practice. Therefore, we used the number of remaining teeth as a measure in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean DMF-T values were 12.99 ± 8.86 in their patient population (prevalence of caries and tooth loss: 83.1% and 83.3%), which were significantly higher in individuals who smoked or who used to smoke; DMF-T values and M values showed significant negative correlation with the Mini-Mental State Examination Scale (MMSE) score, but significant positive correlation with age and the Global Deterioration Scale (GDSRANK) scores, respectively [ 60 ]. A Japanese observational study assessed the oral health status (using the DMF-T index, calculus index [CI], debris index [DI] and Revised Oral Assessment Guide [ROAG]) of hospitalized SCZ patients; significant negative correlations were shown between DMF-T values (mean: 21.7 ± 7.3, higher in males), chlorpromazine equivalents (CPZE) and Barthel index (BI) (denoting mental illness severity), while positive correlations were found with age and length of hospitalization [ 61 ]. Another Spanish case-control study compared the dental and periodontal health status among SCZ patients and controls without psychiatric illnesses: mean dental status indices (D: 4.39, M: 5.66, F: 3.53, DMF-T: 13.51) were lower compared to our study, while the mean periodontal health (expressed using the community periodontal index [CPI]) score was 2.32.…”
Section: Discussionmentioning
confidence: 99%